Exercise Program for Covid-19 Survivors: A Telerehabilitation Framework - YILDIZ ÖZER, AYSEL; AVCI, ENDER ERSİN; TİMURTAŞ, EREN; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Coronavirus disease (COVID-19) is a serious acute respiratory syndrome that has been recognized as a pandemic disease caused by Coronavirus 2 (SARS-CoV-2). The complications related to coronavirus itself, physically inactive period due to symptoms of disease and lockdown may also influence the functional capacities of COVID-19 survivors negatively. It may lead to obstructions in engaging with previous activities of daily living. As a physiotherapy intervention, exercise treatment is one of the novel approaches to support these individuals after the COVID-19 treatment. However, there is limited access to physiotherapy and rehabilitation services during pandemic conditions because of lockdown, especially for infected patients. For increasing accessibility to physiotherapy and rehabilitation care, the World Confederation of Physical Therapy has published a report advising the home-based exercise interventions via Telerehabilitation. Up to date, there is no published framework for structured exercise programs for this population, yet. Since the individual differences in functional levels and possible differences in the severity of coronavirus infection, the physiotherapy, and rehabilitation exercise program should be structured individually for COVID-19 survivors. This document suggests a framework for physical therapists to put into practice an exercise training via telerehabilitation in COVID-19 survivors. The proposed framework has consisted of determination of eligible and risky COVID-19 patients for intervention, physiotherapy assessment tools, 6-week exercise prescription based on FIIT-VP principle (frequency, intensity, time, type, volume, and progression) and criteria for ending exercise.
Keywords: COVID-19; Telerehabilitation; Exercise